2011
DOI: 10.1016/j.chemphys.2011.07.018
|View full text |Cite
|
Sign up to set email alerts
|

A peptide’s perspective of water dynamics

Abstract: This Perspective is focused on amide groups of peptides interacting with water. The 2D IR spectroscopy has already enabled structural aspects of the peptide backbone to be determined through its ability to measure the coupling between different amide-I modes. Here we describe why nonlinear IR is emerging as the method of choice to examine the fast components of the water dynamics near peptides and how isotopically edited peptide links can be used to probe the local water at a residue level in proteins. This ty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
63
0

Year Published

2014
2014
2015
2015

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 56 publications
(71 citation statements)
references
References 87 publications
7
63
0
Order By: Relevance
“…Since that the forward and backward transfer rates are connected through the equilibrium constant, the rate k AB can be calculated from the fitted exchange rates, which is (0.6 ps) −1 , (1.9 ps) −1 , and (0.8 ps) −1 for the drug free, rimantadine bound, and spiran amine bound channels, respectively. Since experiments 47,51,55 and simulations 48 have revealed a timescale of ∼1 ps for hydrogen bond making and breaking for model amides in aqueous solution, these results are thus in accordance with the above mentioned idea that the doublet arises from different hydration/electrostatic states of the Ala30 amide in the same channel.…”
Section: Solvent Exchange Between Amide Sites Exposes Drug-water Isupporting
confidence: 75%
See 4 more Smart Citations
“…Since that the forward and backward transfer rates are connected through the equilibrium constant, the rate k AB can be calculated from the fitted exchange rates, which is (0.6 ps) −1 , (1.9 ps) −1 , and (0.8 ps) −1 for the drug free, rimantadine bound, and spiran amine bound channels, respectively. Since experiments 47,51,55 and simulations 48 have revealed a timescale of ∼1 ps for hydrogen bond making and breaking for model amides in aqueous solution, these results are thus in accordance with the above mentioned idea that the doublet arises from different hydration/electrostatic states of the Ala30 amide in the same channel.…”
Section: Solvent Exchange Between Amide Sites Exposes Drug-water Isupporting
confidence: 75%
“…In bulk water, hydrogen bonds break and form on the timescale of ∼1 ps, which is reflected in the frequency correlation function of small solvated peptides. 47 The timescales measured here indicate that the drug increases the dynamics of the water in the channel, but the dynamics are still slower than in comparison to bulk water. The doublets observed for Gly34 and Ala30 at pH 5, however, make an accurate assessment of their spectral diffusion dynamics difficult, as it has been shown that for overlapping bands, the commonly used metrics, such as the center line slope, do not yield relaxation functions that represent the decay of the underlying frequency-frequency correlation function.…”
Section: Probing Water Dynamics Through Amide Frequency Relaxationsmentioning
confidence: 92%
See 3 more Smart Citations